Effects of temperature and pass number on mechanical properties, microstructure, and texture evolution in pure magnesium processed via a geometrically optimized TCAP method - Mohsen Kamran Masouleh; Amin Mirzakhani; Mohammad Abdian; Ahmad Assempour (Results in Engineering, 2025)
In this study, by optimizing the geometric parameters of the trapezoidal channel, the processing force in the Tubular Channel Angular Pressing (TCAP) process was reduced, and for the first time, 1 mm-thick magnesium tubes were processed using this method. At the beginning of the research, the process was simulated in ABAQUS software using a finite element model, and the effects of geometric parameters on processing force, equivalent strain, and strain inhomogeneity index were investigated. To study the effect of temperature and the number of passes on the improvement of mechanical properties, microstructure, and texture evolution, thin-walled magnesium tubes were processed at 200 °C for three passes and at 250 °C and 350 °C for one pass. With an increasing number of passes, the grain size continuously decreased from the initial 200 µm to 3 µm, and the hardness increased from the initial 30 Vickers to 40 Vickers in the third pass. However, the greatest increase in strength and elongation occurred in the second pass, reaching 1.26 and 1.3 times the initial values, respectively. By increasing the temperature to 250 °C, the ultimate tensile strength rose from the initial 73 MPa to 97 MPa, while increasing the temperature to 350 °C resulted in a decrease in strength to 91 MPa. The observed mechanical properties were closely linked to texture evolution. At 200 °C, a split basal texture formed due to dominant basal slip, while at 250 °C, increased prismatic slip led to grain reorientation and weakening of the basal texture. At 350 °C, static recrystallization (SRX) became the dominant mechanism, promoting grain growth and altering texture distribution. Additionally, dynamic recrystallization (DRX) initially weakened the basal texture, but subsequent recrystallization stabilized grain orientation, enhancing texture sharpening. Overall, the interplay between deformation mechanisms and recrystallization processes determined the final texture evolution, significantly influencing the mechanical properties of TCAP-processed tubes.